THE IRANIAN MASSES AS A SOURCE OF SOCIAL CHANGE: THE REIGN OF MOHAMMAD MOSADDEGH - MITEV, Vladimir (Studia Universitatis Babes-Bolyai Studia Europaea, 2022)
The crowd has played and continues to play a very important role in Iranian politics at critical moments . This article looks at its role in the mid 20th century, especially during the times of rule of Reza Shah (1925-1941) and Mohammad Mosaddegh (1951-1953). The article reviews European thought about the masses, with special emphasis on the ideas of Bulgaria-born Nobel Laureate in Literature Elias Canetti. Canetti believed that the crowd was not always irrational, evil forces, but sometimes played a positive historical role: when it demanded and enacted social change. It is exactly what happened during the times of Mosaddegh. A look at these times is made through excerpts from the Iranian novel Neighbors by Ahmad Mahmoud, through a look at the press of that time and Ervand Abrahamian’s historical writing.